2007
DOI: 10.1177/0363546507308940
|View full text |Cite
|
Sign up to set email alerts
|

Kidney Injuries in Professional American Football

Abstract: Renal trauma is a rare but potentially debilitating injury in the NFL, with players at greater risk during games. Most players recover to play, but it may take some time, especially with a kidney laceration. It may be safe for players with only 1 functioning kidney to play in the NFL.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2010
2010
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(4 citation statements)
references
References 21 publications
0
4
0
Order By: Relevance
“…However, kidney injury during sports participation is extremely rare, with only nine cases per million athletic activities for American Football and even fewer in other sports [70] . Furthermore, none of these injuries resulted in kidney loss [70] , [71] . Based on these data, it seems clear that the benefits of physical activity outweigh the low risk of severe kidney injury and participation by children with a cSFK should be encouraged.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…However, kidney injury during sports participation is extremely rare, with only nine cases per million athletic activities for American Football and even fewer in other sports [70] . Furthermore, none of these injuries resulted in kidney loss [70] , [71] . Based on these data, it seems clear that the benefits of physical activity outweigh the low risk of severe kidney injury and participation by children with a cSFK should be encouraged.…”
Section: Evidence Synthesismentioning
confidence: 99%
“…In the presence of gross hematuria, initial rest is recommended followed by progression of activity with return to play after the microscopic hematuria has resolved [ 11 , 44 , 65 ]. A study of National Football League players revealed an average of 15 days missed for renal contusion and a mean of nearly 2 months for lacerations [ 9 ]. Severe injuries may take 6 to 12 months for full return [ 7 ].…”
Section: Abdomenmentioning
confidence: 99%
“…However, the literature describes renal injuries resulting from football as low-grade with no reports of kidney loss and that all players with renal injuries recovered fully and returned to the sport (Brophy et al, 2008; Wan et al, 2003b; Swischukh, 2006; Waicus & Smith, 1999). Similarly, a case study revealed that a patient with a kidney injury from jujitsu only required monitoring for full recovery and another case study showed that a patient with a renal injury from wrestling needed minimal intervention (Itagaki & Knight, 2004).…”
Section: Literature Reviewmentioning
confidence: 99%